A study of intranasally administered interferon A (rIFN-α2A) for the seasonal prophylaxis of natural viral infections of the upper respiratory tract in healthy volunteers - Tannock, G. A; Gillett, S. M; Gillett, R. S; Barry, R. D; Hensley, M. J; Herd, R.; Reid, A. L. A; Saunders, N. A. (Epidemiology and infection, 1988)
The efficacy of interferon A (rIFN-α2A), an Escherichia coli-derived interferon, in the prophylaxis of acute upper respiratory tract infection, was evaluated in a community-based double-blind placebo-controlled study in the Australian winter of 1985. The trial population of 412 healthy volunteers (190 males and 222 females, aged 18–65 years) self-administered 1·5, 3·0 and 6·0 megaunits (MU) of interferon A per day or a placebo, intranasally for 28 days. The period of study coincided with an outbreak of H3N2 influenza A (detected in 35 of the 107 acute specimens) as well as substantial numbers of respiratory syncytial virus and adenovirus infections. Rhinoviruses were isolated from only three specimens. In many cases, subjects had laboratory and clinical evidence of having had more than one respiratory tract infection during the period of the study. Viruses were detected in 54 or 107 acute specimens (49%). No statistically significant differences were noted between the various treatment groups in the incidence of laboratory-proven viral infection (virus isolation and/or antibody response). Analysis of reported symptoms indicated that blood-tinged mucus and nasal stuffiness occurred more frequently with higher doses of interferon. There appeared to be no clinical benefit from the use of interferon A in the amelioration of symptoms.